Behavioral public administration: combining insights from public administration and psychology - Grimmelikhuijsen, Stephan (2017)
Behavioral public administration is the analysis of public administration from the micro-level perspective of individual behavior and attitudes by drawing on insights from psychology on the behavior of individuals and groups. The authors discuss how scholars in public administration currently draw on theories and methods from psychology and related fields and point to research in public administration that could benefit from further integration. An analysis of public administration topics through a psychological lens can be useful to confirm, add nuance to, or extend classical public administration theories. As such, behavioral public administration complements traditional public administration. Furthermore, it could be a two-way street for psychologists who want to test the external validity of their theories in a political-administrative setting. Finally, four principles are proposed to narrow the gap between public administration and psychology.
Keywords: Psychology; Public administration; Behavioral sciences